Pulmonary Exacerbation of Undiagnosed Toxocariasis in Intensively-Treated High-Risk Neuroblastoma Patients - Szymon Janczar; Monika Bulas; Justyna Walenciak; Dobromila Baranska; Marek Ussowicz; Wojciech Młynarski; Beata Zalewska-Szewczyk (MDPI AG, 2020)
Toxocariasis is one of the most common zoonoses, with high seroprevalence in apparently healthy individuals. Neuroblastoma is an aggressive childhood cancer. The cure rates are improving due to dose-dense chemotherapy, progress in surgical practice, myeloablative therapy with autologous stem cell transplantation, and recently, anti-GD2 immunotherapy. This is associated with a burden of complications, some of which are relatively specific for neuroblastoma treatment. Based on previous reports of Toxocara canis infection in high-risk neuroblastoma patients and cases of pulmonary exacerbation from our center in this disease, we propose that toxocariasis is a specific complication of intensive pediatric cancer treatment and advocate for active surveillance.